Dignity and the capabilities approach in long-term care for older people - Pirhonen, Jari (Nursing philosophy, 2015)
The ageing populations of the Western world present a wide range of economic, social, and cultural implications, and given the challenges posed by deteriorating maintenance ratios, the scenario is somewhat worrying. In this paper, I investigate whether Martha C. Nussbaum's capabilities approach could secure dignity for older people in long-term care, despite the per capita decreases in resources. My key research question asks, ‘What implications does Nussbaum's list of central human capabilities have for practical social care?’ My methodology combines Nussbaum's list with ethnographic data gathered from a Finnish sheltered home for older people. On the basis of this study, it seems that the capabilities approach is a plausible framework for the ethics of care because it highlights differences in the ability to function and thus differences in opportunities to pursue a good life. The ideas presented in this article could assist social policy planners and executives in creating policies and practices that help old people to maintain their dignity until the end of their days.